Mechanistic insight into how multidrug resistant Acinetobacter baumannii response regulator AdeR recognizes an intercistronic region. Issue 16 (17th July 2017) - Wen, Yurong; Ouyang, Zhenlin; Yu, Yue; Zhou, Xiaorong; Pei, Yingmei; Devreese, Bart; Higgins, Paul G; Zheng, Fang
Abstract: AdeR–AdeS is a two-component regulatory system, which controls expression of the adeABC efflux pump involved in Acinetobacter baumannii multidrug resistance. AdeR is a response regulator consisting of an N-terminal receiver domain and a C-terminal DNA-binding-domain. AdeR binds to a direct-repeat DNA in the intercistronic region between adeR and adeABC . We demonstrate a markedly high affinity binding between unphosphorylated AdeR and DNA with a dissociation constant of 20 nM. In addition, we provide a 2.75 Å crystal structure of AdeR DNA-binding-domain complexed with the intercistronic DNA. This structure shows that the α3 and β hairpin formed by β5–β6 interacts with the major and minor groove of the DNA, which in turn leads to the introduction of a bend. The AdeR receiver domain structure revealed a dimerization motif mediated by a gearwheel-like structure involving the D108F109-R122 motif through cation π stack interaction. The structure of AdeR receiver domain bound with magnesium indicated a conserved Glu19Asp20-Asp63 magnesium-binding motif, and revealed that the potential phosphorylation site Asp63 OD1 forms a hydrogen bond with Lys112. We thus dissected the mechanism of how AdeR recognizes the intercistronic DNA, which leads to a diverse mode of response regulation. Unlocking the AdeRS mechanism provides ways to circumvent A. baumannii antibiotic resistance.